2019
DOI: 10.3390/rs11192224
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Mode Impacts on the Sea Level over the Red Sea and Gulf of Aden

Abstract: Falling between seasonal cycle variability and the impact of local drivers, the sea level in the Red Sea and Gulf of Aden has been given less consideration, especially with large-scale modes. With multiple decades of satellite altimetry observations combined with good spatial resolution, the time has come for diagnosis of the impact of large-scale modes on the sea level in those important semi-enclosed basins. While the annual cycle of sea level appeared as a dominant cycle using spectral analysis, the semi-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 61 publications
6
15
0
Order By: Relevance
“…That is consistent with previous studies (Alawad et al, 2019), where, they concluded the close relationship between sea level in the Arabian Sea and ENSO phenomenon during the period of 1993-2017 by using the satellite altimetry. The results indicate the dominance of the negative phase of the IOD and ENSO on the coasts of the Arabian Sea, and this contradicts what it reached in the past.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…That is consistent with previous studies (Alawad et al, 2019), where, they concluded the close relationship between sea level in the Arabian Sea and ENSO phenomenon during the period of 1993-2017 by using the satellite altimetry. The results indicate the dominance of the negative phase of the IOD and ENSO on the coasts of the Arabian Sea, and this contradicts what it reached in the past.…”
Section: Resultssupporting
confidence: 93%
“…The reason may be due to the difference in the two study periods between the records of measuring the tides that extend for long periods that may reach in some stations for more than 50 years and the satellite altimetry data that was created from the end of in 1992. The results may be affected by the strong La Niña event that occurred in 1999-2001 (Alawad et al, 2019). It is known that the negative phase of IOD means that the sea surface temperature is cooler than normal in the western Indian Ocean, including the Arabian Sea.…”
Section: Resultsmentioning
confidence: 99%
“…In spite of these results, the role of large-scale tropical climate modes cannot be ignored, where the RS has direct water exchange with Indian Ocean. Furthermore, recent findings prove the great influence of the El Niño Southern Oscillation on sea level [ 47 49 ] and chlorophyll concentration [ 50 ] in the basin thorough oceanic and atmospheric teleconnections.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations of sea level variability in the Red Sea on time scales from days to decades largely emphasize the role of more local forcing (Abdelrahman 1997;Churchill et al 2018;Cromwell and Smeed 1998;Osman 1984;Patzert 1974;Sofianos and Johns 2001;Sultan and Elghribi 2003;Sultan et al 1995bSultan et al ,c, 1996. However, recent work by Alawad et al (2017Alawad et al ( , 2019 suggests that mean sea level variability in the Red Sea is partly related to large-scale modes of climate variability. These authors reason that this relationship is mediated by westward propagation of off-equatorial Rossby waves originating in the eastern tropical Indian Ocean.…”
Section: Summary and Discussionmentioning
confidence: 99%